The Aspect of Equivalence in Tourism Text - Rahmat Wisudawanto (Faculty of Letters Universitas Balikpapan, 2023)
Tourism texts should achieve their function as promotional texts. The complexity of translating tourism texts requires an appropriate translation technique. The proper translation techniques contribute to the equivalence of translation. This study aims to explain the impact of translation techniques on equivalence. This study used the solo calendar of event 2018 as source of data. Meanwhile, the data is all utterances in the text. The concept of translation as act of communication involves in the study as a parameter in achieving the equivalence. The results indicate the use of translation techniques, namely modulation, literal, calque, and duplet. The most dominant translation techniques is calque while the less dominant is modulation. The achievement of translation equivalence is determined by the target readers' understanding and the text's communication function. The equivalence translation shows the success of the translated text function. Keywords: Translation, Tourism, Techniques, Equivalence, Solo